The contribution of family medicine to community-orientated health services in Mali: A short report - Mahamane M. Maïga; Gabriel Blouin Genest; François Couturier; Sarah Stecko; Michèle Rietmann; Mamadou B. Coulibaly; Drissa M. Sidibé; Fatoumata Dicko (AOSIS, 2021)
Family medicine has not received appropriate attention in the sub-Saharan African context. In particular, family medicine is rarely recognised as a medical speciality and most African countries are silent on the role of family medicine in their health systems. There is, however, an emerging interest in developing family medicine as a key component of primary healthcare. Postgraduate training in family medicine is progressing and many countries have already established specific training programmes. In addition, there have been attempts to define the importance of family medicine, which, we expect, this short report contributes to. Interviews were conducted with physicians, partners and beneficiaries of two international development projects funded by the Canadian government. The one project supports training of health professionals and the other education of healthy women and girls in the community. The objective was to document the strengthening of primary healthcare through the creation and adaptation of a new family and community medicine postgraduate medical programme (which includes both family and community medicine) emphasising field training, immersion in local communities and interdisciplinary collaboration. This article underlines the importance of family medicine in Mali by documenting how what is now termed family and community medicine can promote community-orientated health services. To do so, we use the examples of initiatives and actions done through two international health development projects.